Bond as an alternative financing for BCA Mortgage and mortgage processing service level improvements at BCA consumer loan bandung office - Handoko, Kakan; Sumirat, Erman (The Indonesian Journal of Business Administration, 2013)
Research is performed to find an alternative long-term funding to finance housing loans (mortgages) at PT. BCA, Tbk because BCA have a huge third party funds , but the majority of third-party funds in BCA consists of short-term funds, savings and current accounts. Currently the number of outstanding mortgages are still smaller than the number of long-term funds (time deposits), with projection the increase year on year mortgages much larger than the increase year on year in deposit, so that when the projections made using the average year on year in the last 5 years, the number of outstanding mortgage will exceed the total deposits in 2016. From the analysis of several alternative long-term financing, financing through the issuance of bonds is the most feasible funding for BCA, because of the results of analysis using Flexibility, Risk, Income, Control, and Timing (FRICT) framework, these bonds are best suited for mortgage financing. In addition to the search for alternative sources of long-term funds, in connection with the new regulations of Bank Indonesia on the regulations of the maximum LTV to 70%, causing an increase in mortgage applications were canceled by the prospective borrowers in the Bandung consumer loan office. BCA mortgages in order to continue to grow and compete with other banks need to be done to improve service level of mortgage 5 business days to 3 days, with a simplified mortgage process and change the mortgage regulations. Keywords: FRICT framework for issuance bonds, improving service levels, change the mortgage regulations.